تأثير الصحة الرقمية على حماية الصحة العامة ضد جائحة كوفيد 91 من خلال التأثيرات الوسيطية للتوعية بالصحة - العامة والتغيرات السلوكية: Influence of Digital Health on Public Health Protection Against the COVID-19 Pandemic via the Mediating Effects of Public Health Awareness and Behavioral Changes - بوريش أحمد; تربش محمد; مومني عبد القادر (Journal of North African Economies, 2025)
The purpose of this study was to examine the influence of Digital Health on public health protection against the COVID-19 pandemic via public health awareness and public health behavioral changes as mediating factors in Algeria. Where the applied aspect was dropped on the Multi-Service Clinic “Mukhtari Al Arabi, Nedroma " and to collect the data we used as a tool for study where it was based on 52 questionnaires and after analysis of data using PLS-Smart program. The main findings revealed that the use of Digital Health had a significant positive influence on public health protection against COVID-19 as a pandemic. public health behavioral changes significantly acted as partial mediators in this relationship. Therefore, a better understanding of the effects of the use of Digital Health interventions on public health protection against COVID-19 while taking public health awareness into account as mediator should be helpful when developing any health promotion strategy plan.